Effect of goal difficulty level on volleyball serve learning - Cicero Luciano Alves Costa; Leandro Nogueira Dutra; Glauber Carvalho Nobre; Herbert Ugrinowitsch (Asociación Española de Ciencias del Deporte, 2023)
The purpose of this study was to evaluate the effect of the goal difficulty level on the volleyball serve learning and if the perceived sports competence mediates this process. Adolescent volunteers (N = 22, age = 14.0 ± 0.9 years) participated in this study performing the volleyball serve. Two experimental groups were formed: high difficult goal group (HDG; n = 11) and low difficult goal group (LDG; n = 11). Both groups performed 15 trials in the pretest, 160 trials in the acquisition throughout four days, and 15 trials in the retention test after 72 hours. Performance was measured by means of the target bull's-eye accuracy of the volleyball serve. Comparing the two groups' performance accuracy and consistency on pretest and retention tests was run through two-way ANOVA and ANCOVA (2 Groups x 2 Blocks). The results showed high goal led to greater performance accuracy in the retention than the lower goal, with a very large effect size. The HDG had higher accuracy in the retention test than the pretest (p < .001), while the LDG had no improvement. ANCOVA detected significant between the covariate perceived sport competence and tests. The effect size magnitude of the high goal difficulty in the serve accuracy was higher when adjusted by perceived sports competence. This finding indicates that perceived sports competence could maximize goal difficulty effectiveness. In conclusion, the goal with high difficulty is more effective for volleyball serve learning than low difficulty, and the perceived sports competence seems to moderate the learning process.